ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study was conducted aimed to determine whether the Debt to Equity Ratio, Public Accounting Firm, Size, Earnings per Share and Return on Equity affects the value of the company in LQ-45 firms listed on the Indonesia Stock Exchange.Independent variable in this study was measured by Debt to Equity Ratio, Public Accounting Firm, Size , Earnings per Share and Return on Equity. The samples used in this study were 27 companies with a purposive sampling technique. The empirical results of this study using the method of analysis is multiple linear regression analysis.The results of this research can be concluded that the Debt to Equity Ratio, the Office of the Public Accountant, Size, and Earnings Per Share has no effect on the value of the company. While the Return On Equity, affect the value of the company.Keywords: Debt to Equity Ratio, the Office of the Public Accountant, Size, Earning Per Share, Return on Equity, the Value of the Company